Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Differentiate the function f(x)=x^3 in the point a. Use the definition of the derivative for this question. I know that the definition of the derivative is:

$$f'(x) = \lim_{h\to 0}\frac{f(x+h)-f(x)}{h}$$

The function $f(x)=x^3$ Now to the the derivative...

I know that $h$ means $\Delta x$. I know that $\Delta x$ means $\Delta x = x_2-x_1 \implies x_2 = x_1 + \Delta x$

I'm just not sure how to obtain the derivative do to the function has an exponent.

Here's my attempt:

$$f'(x) = \lim_{h\to 0}\frac{x^3(x+x^3+x^3)-x^3}{h}$$ Then I got: $$f'(x) = \lim_{h\to 0}\frac{x^3(x + 2 x^3)-x^3}{2x^3}$$ Simplified: $$f'(x) = \lim_{h\to 0}= x$$

I know I did something wrong, because WolframeAlpha says: $\frac{d}{dx}(x^3) = 3 x^2$

I just don't see where exactly I did wrong. (If the problem is obvious and I didn't see it I'm sorry, but I'm currently clueless on how to solve this.)

share|cite|improve this question
up vote 2 down vote accepted

If $f(x)=x^3,f(x+h)=(x+h)^3,$


So, $$\lim_{h\to 0}\frac{f(x+h)-f(x)}h=\lim_{h\to 0}\frac{h\{(x+h)^2+(x+h)x+x^2\}}h$$

$$=x^2+x^2+x^2$$ as $h\ne0$ as $h\to0$

Alternatively, $f(x+h)-f(x)=(x+h)^3-x^3=x^3+3x^2h+3xh^2+h^3-x^3=h(3x^2+3xh+h^2)$

$$\lim_{h\to 0}\frac{f(x+h)-f(x)}h=\lim_{h\to 0}\frac{h(3x^2+3xh+h^2)}h=3x^2$$ as $h\ne0$ as $h\to0$

share|cite|improve this answer
Thank you so much, I see want I did wrong. – Kami Mar 18 '13 at 11:06
@user67254, my pleasure. A practice of $f(x+h)$ based on $f(x)$ can be handy. Like for $f(x)=x^x,x^{\sin x},\cos(\ln x)$ etc. – lab bhattacharjee Mar 18 '13 at 11:13

Using the Identity

$$a^3-b^3=(a-b)(a^2+a\cdot b+b^2)$$

We can solve the derivative of


using the definition of derivative

$$f'(x) = \lim_{h\to0}{\frac{f(x+h) - f(x)}{h}}$$ $$=\lim_{h\to0}\frac{(x+h-x)((x+h)^2+(x+h)\cdot(x)+x^2)}{h}$$ $$=\lim_{h\to0}((x+h)^2+(x+h)\cdot(x)+x^2)$$ $$=(x)^2+(x)\cdot(x)+x^2$$ $$=3\cdot x^2$$

share|cite|improve this answer

Where this $x^3(x+x^3+x^3)$ is coming from? You'd rather substitue $(x+h)$ in place of $x$ when $f$ is to be applied:


share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.